514 Late-Breaking: Effects of Feeding a High Canola Meal-containing Diet and Multi-carbohydrase Supplementation on Growth Performance and Intestinal Ecology of Piglets. (8th October 2021) - Holanda, Debora; Regassa, Alemu; Patterson, Robert; Nyachoti, Martin
Abstract: The objective was to investigate the effects of a high canola meal-containing diet and multi-carbohydrase supplementation on growth performance and intestinal pH, short-chain fatty acid (SCFA) profile, and microbiome in weaned piglets. Twenty-four piglets (7.46 ± 0.23 kg BW) were individually assigned to 1 of 3 diets in a completely randomized design. Diets were fed for 21 d: SB, corn and soybean meal-based diet; CM, 25% canola meal substituting soybean meal and adjusted to meet energy and nutrient requirements of piglets (NRC, 2012); and CM+E, CM supplemented with multi-carbohydrase (0.01%). Feed disappearance and BW were recorded weekly. On d 21, piglets were euthanized to assess digesta pH, SCFA profile, and gut microbiome. Data were analyzed using the MIXED procedure of SAS using the piglet as the experimental unit. There were no differences (P > 0.10) in growth performance and digesta pH. Piglets fed CM+E tended to (P = 0.051) or had significantly lower (P < 0.05) butyric acid in the cecum than piglets fed CM and SB, respectively. Piglets fed SB had higher (P < 0.05) isobutyric acid in the colon than piglets fed CM+E. Piglets fed SB and CM tended to have higher (P < 0.05) isovaleric acid in the colon than piglets fed CM+E. Piglets fed SB tended to have lower (P < 0.10) proportion of Bifidobacteria, and had lower (P < 0.05) Enterobacteriaceae, Enterococcus, and Lactobacillus than piglets fed CM. Piglets fed CM+E tended to have lower (P < 0.10) Bifidobacteria and higher Clostridium XIVa than piglets fed CM, and had lower (P < 0.05) Enterococcus, but higher (P < 0.05) Lactobacillus than piglets fed CM. In conclusion, feeding 25% of canola meal in substitution to soybean meal with or without multi-carbohydrase supplementation changed the intestinal environment by modifying SCFA profile and relative proportion of microbiome, but without affecting digesta pH or growth performance in nursery piglets.